Strengthening The Power of The Essence of Contemporary Learning Theory in Responding to The Problems of Islamic Education - Iwan Iwan; Arib Mubarok (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Learning is a process that happens to everyone and lasts a lifetime (from infancy until death). One of the signs of learning is a change in behaviour in life (cognitive, psychomotor, and affective). Behaviourism is a philosophy in psychology based on the proposition that everything an organism does, including actions, thoughts, or feelings, can and should be considered behavioural. For learning to develop children's intellectual skills in learning something knowledge (for example, a mathematical concept), the subject matter needs to be presented by taking into account the child's stage of cognitive development/knowledge so that the knowledge can be internalized in the mind (cognitive structure) of the person. In meaningful learning, there needs to be development and collaboration of concepts. The way inclusive elements are introduced first and then in more detail.